2013
DOI: 10.1124/dmd.113.051391
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Metabolism Notably Affects Human Systemic Exposure to Ginsenosides from Orally Administered Extract of Panax notoginseng Roots (Sanqi)

Abstract: Ginsenosides are medicinal ingredients of the cardiovascular herb Panax notoginseng roots (Sanqi). Here, we implemented a human study (ChiCTR-ONC-09000603; www.chictr.org) to characterize pharmacokinetics and metabolism of ginsenosides from an orally ingested Sanqi-extract (a 1:10 water extract of Sanqi) and the human plasma and urine samples were analyzed by liquid chromatographymass spectrometry. Plasma and urinary compounds derived from ginsenosides included: 1) intestinally absorbed ginsenosides Ra 3 , Rb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 20 publications
0
55
0
Order By: Relevance
“…An herbal constituent can be defined as drug-like if it possesses the desired pharmacologic potency, a wide safety margin, appropriate pharmacokinetic (PK) properties, and adequate content in the medicine dosed. Recent multicompound PK studies have indicated that human subjects and laboratory animals are considerably exposed to only a few constituents of an herbal medicine after dosing (Lu et al, 2008;Liu et al, 2009;Li et al, 2012a;Chen et al, 2013;Cheng et al, 2013;Hu et al, 2013;Jiang et al, 2015;Li et al, 2015). Such PK studies provide information for pharmacologists regarding which herbal compounds merit further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…An herbal constituent can be defined as drug-like if it possesses the desired pharmacologic potency, a wide safety margin, appropriate pharmacokinetic (PK) properties, and adequate content in the medicine dosed. Recent multicompound PK studies have indicated that human subjects and laboratory animals are considerably exposed to only a few constituents of an herbal medicine after dosing (Lu et al, 2008;Liu et al, 2009;Li et al, 2012a;Chen et al, 2013;Cheng et al, 2013;Hu et al, 2013;Jiang et al, 2015;Li et al, 2015). Such PK studies provide information for pharmacologists regarding which herbal compounds merit further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…(2)-Epicatechin was used as the positive control to assess the catechol-O-methyltransferase (COMT) activities of the human, rat, and dog liver cytosols (Zhu et al, 2000;Li et al, 2012), and the in vitro t 1/2 values were 0.46, 0.08, and 0.21 hour, respectively. 7-Hydroxyflavone was used as the positive control to assess the sulfotransferase (SULT) activities of the human, rat, and dog liver cytosols (Li et al, 2012;Hu et al, 2013), and the in vitro t 1/2 values were 0.07, 0.29, and 0.10 hour, respectively. Chrysin was used as the positive control to assess the UDP-glycosyltransferase (UGT) activities of the human, rat, and dog liver microsomes (Li et al, 2012;Hu et al, 2013), and the in vitro t 1/2 values were 0.08, 0.05, 0.05 hour, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is hypothesized that the active principles responsible for the therapeutic effects of an herbal medicine come from a few constituents with favorable drug-like properties, including the desired pharmacologic potency, a wide safety margin, appropriate pharmacokinetic (PK) properties, and adequate content in the dosed medicine [9,10] . Recent multicompound PK studies of herbal medicines indicate notable differences between the circulating herbal compounds and the chemical ingredients of the dosed medicine [9,[11][12][13][14][15][16][17] . Pharmacologically active herbal compounds that exhibit considerable levels of body exposure after dosing an herbal medicine are the most likely to form the basis of therapeutic efficacy of the medicine.…”
Section: Introductionmentioning
confidence: 99%